Ceramic production at Selinunte (Sicily) during the 4th and 3rd century BCE: New archaeometric data through the analysis of kiln wastes. (December 2018) - Montana, G.; Randazzo, L.; Tsantini, E.; Fourmont, M.
Abstract: A set of 37 overfired ceramic samples was collected from the dump of two kilns sited in the productive area FF1 in the acropolis of Selinunte (south western Sicily), being specifically active in the period 409–250 BCE. The ceramic samples were analysed by thin-section petrography and chemical analysis, with the aim to establish a valuable 'reference group' representative of the ceramic produced at Selinunte during the Punic phase. The petrographic and chemical analyses allowed to state that the ceramic manufactures from the kilns operating in the FF1 insula are characterized by rather homogeneous textural/compositional features. The daily-use common ware here produced is characterized by aplastic inclusions mainly falling in the size classes of coarse silt and medium sand, with relative abundance ranging between 15 and 25% area. The inclusions are composed of monocrystalline quartz and, subordinately, of calcareous bioclasts, polycrystalline quartz, K-feldspar, plagioclase, chert, sandstones and acid rock fragments. The relatively low total chemical variability of the ceramic sample set reflects the specific incidence of the above-mentioned mineralogical and textural features. The variable amount of quartz-rich sand used for tempering the local raw clays produces slight variations in the SiO2 /CaO concentration ratio. Nonetheless, the chemical 'reference group' defined through this study seems to be consistent and characterized by satisfactory low standard deviations and it is fully congruent with the geo-lithological background of the area. This new chemical 'reference group' might be applied to studies that are aimed to define the trade networks in that time in south western Sicily. It could also represent a useful starting point for future systematic studies concerning various ceramics classes (i.e. tableware, cooking ware, transport amphorae, etc.), taking into account the consumption and insular/extra insular trade dynamics of the ceramic products of Punic Selinunte. Highlights: Analysis of ceramic produced at Selinunte throughout the 4th–3rd century BCE Definition of a chemical reference group by the analysis of overfired kiln wastes Comparison with clayey materials available in the area and local Archaic ceramic New insights for the definition of ceramic trade dynamics of the Punic Selinunte